Pengaruh Komitmen Managemen, Kompetensi Pekerja, Budaya K3 terhadap Keselamatan Kerja yang Berdampak terhadap Kinerja Perusahaan PT Adhi Karya (Persero) Tbk - Sutarto Sutorto; Aam Bastaman (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research examines the influence of management commitment, worker competency, K3 culture on work safety which has an impact on PT company performance. Adhi Karya (Persero) tbk. The sample used in this research was employees of PT. Adhi Karya (Persero) tbk using a side purposive technique where from the results of the sample criteria 100 sample respondents were used in this research. The results of the research conducted show that management commitment, competence, K3 culture, work safety have a positive and significant effect on company performance, while management commitment, competence, K3 culture have a positive and significant effect on work safety, organizational K3 culture has a positive and significant effect on safety. work. Management commitment, competence, K3 culture, work safety have a positive and significant effect on company performance with work safety as a mediating variable. In conclusion, there is a significant and positive influence between employee competency management commitment, K3 culture on work safety so that it has an impact on company performance Keywords: Management commitment, competency, K3 culture, work safety, performance